Синтез новых производных изатина, содержащих 1,2,3-триазольное кольцо - Галстян, А. С.; Еганян, Т. А.; Кочикян, Т. В. («Գիտություն» հրատ.)
Взаимодействием N-пропаргилизатина с бензилазидами в условиях CuAAC (Cu-catalyzed azide-alkyne cycloaddition) клик реакции были получены соответствующие 1,2,3-триазолоизатины с хорошими выходами. На базе последних получены соответствующие тиосемикарбазоны, которые могут являться синтонами для построения новых гетероциклических систем. N-պրոպարգիլիզատինի և բենզիլազիդների փոխազդեցությունից CuAAC քլիք ռեակցիայի պայմաններում սինթեզվել են բարձր ելքերով համապատասխան 1,2,3-տրիազոլոիզատինի ածանցյալներ։ Վերջիններիս հիման վրա ստացվել են համապատասխան թիոսեմիկարբազոններ, որոնք կարող են լավ ելանյութեր դառնալ նոր հետերոցիկլիկ համակարգերի կառուցման համար։ The reaction of N-propargyl isatin with benzyl azides under CuAAC click reaction conditions yielded the corresponding 1,2,3-triazoloisatinеs in good yields. The synthesized 1,2,3-triazolylisatins were previously described in the literature, where these substances were used as synthons for the synthesis of bioactive substances; however, the melting points of 1,2,3-triazolylisatins described in the literature differ from those obtained by us, which apparently can be explained by the purity of the obtained substances. On the basis of the latter, the corresponding thiosemicarbazones have been obtained, which can be good synthons for the construction of new hete-rocyclic systems.
Keywords: Քիմիա